Respuesta :
Answer:
2/3
Step-by-step explanation:
Simplify 2/6 to 1/3. Simplify 4/12 to 1/3. Since they have common denominators, add the numerators. 1/3 + 1/3= 2/3
The answer is : 2/3 !!
1.
if u simply 4/12 , it becomes 2/6 , since 6*2=12 so u divide 12 by 2, and 4 by 2, making it 2/6.
2. So 2/6 +2/6 = 4/6 !
( you only add the numerator to eachother!)
And if u look at it,
- 4 divided by 2 = 2
—
- 6 divided by 2 = 3
So u take 4 (the original numerator) and switch it to 2
And switch the 6 (the original denominator) into 3 !!
Making it 2/3 !
1.
if u simply 4/12 , it becomes 2/6 , since 6*2=12 so u divide 12 by 2, and 4 by 2, making it 2/6.
2. So 2/6 +2/6 = 4/6 !
( you only add the numerator to eachother!)
And if u look at it,
- 4 divided by 2 = 2
—
- 6 divided by 2 = 3
So u take 4 (the original numerator) and switch it to 2
And switch the 6 (the original denominator) into 3 !!
Making it 2/3 !